PENGEMBANGAN MODEL PEMBELAJARAN BERDIFERENSIASI BERBASIS KOMUNITAS BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR PADA MAPEL BAHASA INDONESIA SISWA KELAS 3 SEKOLAH DASAR KECAMATAN DUMBO RAYA - Ayu; Rusmin Husain; Rusdin Djibu (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to develop differentiated teaching modules based on learning communities to improve student learning outcomes. The research uses the Research and Development (R&D) method with the ADDIE development model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The approach used is a mix-method, which is a combination of qualitative and quantitative approaches. The results of the study show that the teaching modules developed have gone through a validation process by material and media experts with "very feasible" results. The implementation of the module in the experimental classroom for four weeks showed a significant improvement in student learning outcomes compared to the control class. The involvement of the learning community (teachers, students, and parents) in the process of developing and implementing the modules also plays an important role in creating a collaborative learning environment, responsive to student needs, and encouraging active involvement in learning. Thus, community-based differentiated teaching modules are effectively implemented as a solution to accommodate student diversity in learning and can improve the quality of education as a whole.